Combinatorial therapeutic strategies for enhanced delivery of therapeutics to brain cancer cells through nanocarriers: current trends and future perspectives - Xiande Wang; Cheng Wu; Shiming Liu; Deqing Peng (Taylor & Francis Group, 2022)
Brain cancer is the most aggressive one among various cancers. It has a drastic impact on people's lives because of the failure in treatment efficacy of the currently employed strategies. Various strategies used to relieve pain in brain cancer patients and to prolong survival time include radiotherapy, chemotherapy, and surgery. Nevertheless, several inevitable limitations are accompanied by such treatments due to unsatisfactory curative effects. Generally, the treatment of cancers is very challenging due to many reasons including drugs' intrinsic factors and physiological barriers. Blood-brain barrier (BBB) and blood-cerebrospinal fluid barrier (BCSFB) are the two additional hurdles in the way of therapeutic agents to brain tumors delivery. Combinatorial and targeted therapies specifically in cancer show a very promising role where nanocarriers' based formulations are designed primarily to achieve tumor-specific drug release. A dual-targeting strategy is a versatile way of chemotherapeutics delivery to brain tumors that gets the aid of combined ligands and mediators that cross the BBB and reaches the target site efficiently. In contrast to single targeting where one receptor or mediator is targeted, the dual-targeting strategy is expected to produce a multiple-fold increase in therapeutic efficacy for cancer therapy, especially in brain tumors. In a nutshell, a dual-targeting strategy for brain tumors enhances the delivery efficiency of chemotherapeutic agents via penetration across the blood-brain barrier and enhances the targeting of tumor cells. This review article highlights the ongoing status of the brain tumor therapy enhanced by nanoparticle based delivery with the aid of dual-targeting strategies. The future perspectives in this regard have also been highlighted.